2017
DOI: 10.1002/14651858.cd007417.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids as adjuvant therapy for ocular toxoplasmosis

Abstract: Background Ocular infection caused by Toxoplasma gondii, a parasite, may result in inflammation in the retina, choroid, and uvea, and consequently lead to complications such as glaucoma, cataract, and posterior synechiae. Objectives The objective of this systematic review was to assess the effects of adjunctive use of corticosteroids to anti-parasitic therapy versus anti-parasitic therapy alone for ocular toxoplasmosis. Search methods We searched CENTRAL (which contains the Cochrane Eyes and Vision Trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
1
21
0
2
Order By: Relevance
“…Steroids are generally started a few days after initiation of antimicrobial therapy and continued for about 1 month, with gradual tapering (109,136). It should be acknowledged that the evidence for adjuvant steroids is not based on high-quality data (149), and steroids must not be used without concomitant antimicrobial therapy, as this can lead to a complete loss of vision.…”
Section: Ocular Toxoplasmosismentioning
confidence: 99%
“…Steroids are generally started a few days after initiation of antimicrobial therapy and continued for about 1 month, with gradual tapering (109,136). It should be acknowledged that the evidence for adjuvant steroids is not based on high-quality data (149), and steroids must not be used without concomitant antimicrobial therapy, as this can lead to a complete loss of vision.…”
Section: Ocular Toxoplasmosismentioning
confidence: 99%
“…12 Concomitant prednisolone therapy of 0.5 to 1 mg/kg daily is also often used to reduce inflammation, although there is limited evidence from randomized clinical trials demonstrating their effectiveness as an adjuvant therapy. 13,14 However, steroids should not be used as monotherapy (without antibiotics), or in the immunocompromised patient due to the high probability of inducing fulminant retinochoroiditis. 15 A study by Faridi et al of 35 eyes of 28 patients diagnosed with ocular toxoplasmosis showed that 11.4% of patients developed RD which led to severe vision loss despite successful RD repair.…”
Section: Discussionmentioning
confidence: 99%
“…In diesem Kollektiv fand sich auch ein medianes rezidivfreies Intervall von 3 Jahren, unabhängig davon, ob keine oder eine toxoplasmosespezifische Antibiotikatherapie durchgeführt wurde, wohingegen eine alleinige systemische Kortisontherapie ohne Antibiotika das rezidivfreie Intervall auf 0,9 Jahre reduzierte [41]. Eine alleinige Kortikosteroidtherapie scheint damit obsolet, wohingegen eine adjuvante Anwendung von Steroiden zusätzlich zu Antibiotika sehr variabel gehandhabt wird, da evidenzbasierte Richtlinien zur Höhe und Dauer der begleitenden Steroidtherapie nicht existieren [34,35,41,44]. [15,16].…”
Section: Ergebnisseunclassified